A REVIEW ON SANDHIVATA (OSTEOARTHRITIS) AND ITS MANAGEMENT THROUGH AYURVEDA - Gunjan Sabarwal,; Vikas Prajapati,; Shivakumar S Harti,; Medha Sanjay Kulkarni, (International Journal of Ayurveda and Pharma Research, 2020)
In the present era Sandhivata is the most common disease affecting a large population. Sandhivata term is derived from words as “Sandhi” and “Vata”. When Vata lodges in Sandhi (joints), it is characterized by pain, swelling, and restriction of joint movement. The clinical presentation of Sandhivata closely mimics with the disorder called Osteoarthritis which is the second most common rheumatologic problem. Sandhivata is the disease mentioned in Ayurveda and is a type of Vatavyadhi which most commonly occurs in Vridhavastha due to Dhatukshaya. Sandhivata is one of the challenging diseases for the clinicians due to its chronicity, incurability, complications etc. The allopathic treatment provides the symptomatic relief but the underlined pathology remains untreated due to absence of effective therapy and also giving rise to many side effects, toxic effects and adverse reactions. The treatment procedure described in Ayurveda focuses not only on drugs but also lifestyle modification thus having a holistic approach in its management. So, the present study deals with systemic review of Sandhivata and the aim of this work is to review and highlight the effectiveness of different Ayurvedic interventions in patients with osteoarthritis (OA).